[3–√+2–√3–√−2–√−3–√−2–√3–√+2–√]simplifies to = ?[3+23−2−3−23+2]simplifies to = ?\eqalign{ & \left[ {\frac{{\sqrt 3 + \sqrt 2 }}{{\sqrt 3 - \sqrt 2 }} - \frac{{\sqrt 3 - \sqrt 2 }}{{\sqrt 3 + \sqrt 2 }}} \right] \cr & {\text{simplifies to = ?}} \cr} " /> [3–√+2–√3–√−2–√−3–√−2–√3–√+2–√]simplifies to = ?[3+23−2−3−23+2]simplifies to = ?\eqalign{ & \left[ {\frac{{\sqrt 3 + \sqrt 2 }}{{\sqrt 3 - \sqrt 2 }} - \frac{{\sqrt 3 - \sqrt 2 }}{{\sqrt 3 + \sqrt 2 }}} \right] \cr & {\text{simplifies to = ?}} \cr} " /> [3–√+2–√3–√−2–√−3–√−2–√3–√+2–√]simplifies to = ?[3+23−2−3−23+2]simplifies to = ?\eqalign{ & \left[ {\frac{{\sqrt 3 + \sqrt 2 }}{{\sqrt 3 - \sqrt 2 }} - \frac{{\sqrt 3 - \sqrt 2 }}{{\sqrt 3 + \sqrt 2 }}} \right] \cr & {\text{simplifies to = ?}} \cr} " />
Post your Comments